Efecto de la adición en el agua de bebida de un inmunomodulador antiestresante en las etapas de preinicio, inicio y crecimiento de pollos de carne de la Línea COBB 5OO - Barrera Rebaza, Alida Lisset (2011)
The ! present work of investigation had like obj ective to evaluate the effect of an Imrnunomodulating antiestresante in the stages of pre-beginning, beginning and 1 growth ofmeat chickens ofthe line Cobb 500. The evaluated parameters were: gain 1 of )Veight, food consumption, nutritional conversion, mortality and index of productive efficiency (I. P. E). Eight hundred birds distributed at random in two treatments, experimental witness were used. To the experimental treatment him pro~ision in the drink water the immunomodulating antiestresante in the stage ofPre- 1 Beginning: 0.30ml, in the stage of Beginning: 0.35ml and in the stage of Growth: 1 0.3~m1 respectively. The used estadisctic design was Design ofBlocks Completeíy at Random. The major increases of alive weight were in MALE experimental treatments EXP (3107.60g) and EXP FEMALE (2504.70g) with respect to the tre~tments witnesses, MALE TEST (3006.20g) and TEST FEMALE (2336.50g), the 1 maj,<)fs final alive weights presented MALE treatments EXP (3155.20g) and EXP 1 FEJYIALE (2550.00g) with respect to MALE TEST (3053.30g) and TEST FEMALE (2381.90g). As much MALE EXP as EXP FEMALE presented significant differences (p<0.05) in front ofMALE TEST and TEST FEMALE as ofthe 21 days. The majors food consumptions appeared in MALE EXP (5233.90g) and EXP FEMALE (4659.30g) with respect to MALE TEST (5113.10g) and TEST FEMALE 1 (45!13.00g). The best nutritional conversions presented MALE EXP (1.68) and EXP 1 FEI~1ALE (1.86) with respect to MALE TEST (1.70) and TEST FEMALE (1.93). Smf!ller mortaJüjes presented MALE EXP (1,0%) and EXP FEMALE (1,5%), whereas for MALE TEST and TEST FEMALE he was 2,0%. The best I.P.E. 1 presented MALE EXP (442) and EXP FEMALE (321) followed by MALE TEST 1 1 with 419 and TEST FEMALE with 288. For food consumption and nutritional conversion were significant differences (p<0.05) between treatments, for mortality, 1 were not significant differences (p~0.05). One concludes that with the addition of an im~unomodulating antiestresante I improve the evaluated productive parameters in meat chickens.